The Artist’s Intent in Flux - Rebecca Gordon; Erma Hermens (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper questions whether the concept of the artist’s intent and its connection with the physical fabric of an object/artwork still holds sway. It outlines some ways in which the artist’s intent can be identified and raises issues of reliability and value that often result in it being viewed with some reservation. This will be explored specifically in relation to modern and contemporary art in order to promote a rounded approach to the interpretation and conservation of a work of art.